Seen and Unseen Worlds. (Rowman & Littlefield Publishing Group, Inc., 2012)
Since 451 A.D., at the Council of Chalcedon, Christians have prayed a credo-a short summary of their belief-during Mass which begins: "I believe in God, the Father Almighty, Maker of Heaven and earth and of all things seen and unseen." With that belief, they see the unseen: God, His Blessed Mother, the Angels, the Saints, and Satan, the fallen Archangel. This touching memoir asserts the fact that we live in two different worlds-the ever-changing one we see with our human eyes and the ever-constant one we see with our eyes of faith. Seen and Unseen Worlds: Private Memoirs of a Former Jesuit is a very human introduction to living faith by a young man who was part of the Society of Jesus (the Jesuits) for nearly twelve years. The book culminates with Murray's decision to leave the Society in 1956. This book is for people of all religions and ages because it deals with life, destiny, the world we know, and the world we cannot yet know.
1 Meanderings of a Muddled Heart 1 -- 2 A Boy's Thoughts 12 -- 3 Systematic Contradictions 27 -- 4 Ignatius of Loyola 48 -- 5 The "Long Retreat" 61 -- 6 The Pierian Spring 110 -- 7 The Art of Wonder 124 -- 8 Schoolmasters 150 -- 9 Yearnings of the Heart 168 -- 10 Directives and Secrets 171.
Includes bibliographical references.
Added to collection customer.56279.3
Keywords: Murray, J. Richard; Jesuits -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Institutions & Organizations; Electronic books